Blood reference intervals for rabbits (Oryctolagus cuniculus) from routine diagnostic samples - Leineweber, Christoph; Müller, Elisabeth; Marschang, Rachel E. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Objective: The goal of this study was to establish reference intervals for blood parameters in rabbits based on data from routine diagnostic samples. Materials and methods: Data sets from 1679–2039 values for clinical chemistry and 937–1559 values for hematological parameters were evaluated using the statistical program Reference Limit Estimator 20151017. Results: The following reference intervals were calculated for hematology: erythrocytes 4.37–7.43 × 1012 cells/l; hematocrit 0.28–0.48 l/l; hemoglobin 89.63–153.82 g/l; leucocytes 2.71–12.23 × 109 cells/l; neutrophils 0.87–7.82 × 109 cells/l; lymphocytes 0.36–6.58 × 109 cells/l; monocytes 0.08–1.71 × 109 cells/l; eosi nophils 0.07–0.19 × 109 cells/l; basophils 0.06–1.1 × 109 cells/l; thrombocytes 225.45–905.3 × 109 cells/l. Calculated intervals for clinical chemistries were: alkaline phosphatase 9.05–94.68 U/l; aspartataminotransferase 3.75–32.44 U/l; creatine kinase 1.63–559.53 U/l; γ-glutamyltransferase 2.5–14.46 U/l; glutamatdehydrogenase 0.68–14.78 U/l; fructosamin 248.08–501.43 µmol/l; bile acid 0.76–19.63 μmol/l; total protein 48.66–73.64 g/l; urea 2.63–10.28 mmol/l; creatinine 51.38–154.35 µmol/l; calcium 3.02–4.3 mmol/l; magnesium 0.66–1.51 mmol/l; phosphorus 0.54–2.18 mmol/l; sodium 132.61– 154.0 mmol/l and potassium 3.52–6.04 mmol/l. Conclusion and clinical relevance: The calculation of intervals based on a large number of routine diagnostic samples allows the establishment of labora tory specific reference intervals without the use of experimental animals.
Keywords: Hematology; biochemistry; Reference Limit Estimator; parameter; small mammals